KADAR PROTEIN S100B SERUM 120 JAM PERTAMA SEBAGAI FAKTOR PROGNOSTIK PADA CEDERA KEPALA BERAT - Ridha Dharmajaya (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION SECONDARY BRAIN DAMAGE AFTER HEAD INJURY HAVE WORSE EFFECTS THAN THE PRIMARY ONE THE PROCESS OF SECONDARY BRAIN DAMAGE SHOULD BE MINIMIZED TO OBTAIN MAXIMUM RESULT OF PATIENT MANAGEMENT AND THEREFORE A PRECISE MARKER IS NEEDED S100B PROTEIN IS A CALCIUMBINDING PROTEIN THAT INCREASES RAPIDLY AFTER HEAD INJURY AND THUS A MARKER OF MOLECULAR BRAIN DAMAGE HOWEVER IT IS STILL BEING QUESTIONED AT WHICH TIME SERUM S100B LEVEL WILL SHOW AN ASSOCIATION WITH PATIENTS OUTCOME